Plant and carabid beetle species diversity in relation to forest type and structural heterogeneity (European Journal of Forest Research, 2008)
The aim of this study was to evaluate the inﬂuence of forest structure (mainly resulting from human uses) and forest type (the identity of the dominant tree species) on biodiversity. We determined the diversity of two taxonomical groups: the understory vegetation and the edaphic carabid beetle fauna. We selected eight types of forest ecosystems (ﬁve replicates or stands per forest type): pine (Pinus sylvestris) plantations of three age classes (10, 40 and 80 years since reforestation), an old-growth relict natural pine forest, and four types of oak (Quercus pyrenaica) stands: mature forests with livestock grazing and ﬁrewood extraction, mature forests where uses have been abandoned, ‘‘dehesa’’ ecosystems and shrubby oak ecosystems. The results obtained by a global PCA analysis indicated that both tree size and dominant species inﬂuenced the ordination of the 40 forest stands. In general, carabids were more sensitive to changes in forest heterogeneity and responded more clearly to the analysed structural variables than the understory vegetation, although the species richness of both groups was signiﬁ- cantly correlated and higher in case of oak forests. Pine forest ecosystems were characterised by the lowest species richness for both taxonomical groups, the lowest plant diversity and by the lowest coefﬁcients of variation and, consequently, low structural heterogeneity. As a result, it was very difﬁcult to discriminate the effects of the spatial heterogeneity and the dominant tree species on biodiversity

Plant and carabid beetle species diversity in relation to forest type and structural heterogeneity - Taboada, Ángela; Tárrega, Reyes; Calvo, Leonor; Marcos, Elena; Marcos, José Antonio; Salgado, José María (European Journal of Forest Research, 2008)
The aim of this study was to evaluate the inﬂuence of forest structure (mainly resulting from human uses) and forest type (the identity of the dominant tree species) on biodiversity. We determined the diversity of two taxonomical groups: the understory vegetation and the edaphic carabid beetle fauna. We selected eight types of forest ecosystems (ﬁve replicates or stands per forest type): pine (Pinus sylvestris) plantations of three age classes (10, 40 and 80 years since reforestation), an old-growth relict natural pine forest, and four types of oak (Quercus pyrenaica) stands: mature forests with livestock grazing and ﬁrewood extraction, mature forests where uses have been abandoned, ‘‘dehesa’’ ecosystems and shrubby oak ecosystems. The results obtained by a global PCA analysis indicated that both tree size and dominant species inﬂuenced the ordination of the 40 forest stands. In general, carabids were more sensitive to changes in forest heterogeneity and responded more clearly to the analysed structural variables than the understory vegetation, although the species richness of both groups was signiﬁ- cantly correlated and higher in case of oak forests. Pine forest ecosystems were characterised by the lowest species richness for both taxonomical groups, the lowest plant diversity and by the lowest coefﬁcients of variation and, consequently, low structural heterogeneity. As a result, it was very difﬁcult to discriminate the effects of the spatial heterogeneity and the dominant tree species on biodiversity
Keywords: Biodiversity; carabid beetles; heterogeneity; oak forests; pine plantations; understory vegetation